Determinants of Funding Decision: Empirical Evidence from Companies Listed in Indonesia Stock Exchange - Risnaeni, Eva Yuni; Khoiruddin, Moh (Management Analysis Journal, 2021)
The funding decision is an important decision for the company because this is the main decision in financial management that will directly influence the company’s financial position. The phenomenon from 2014-2018 describes that companies listed on the Indonesia Stock Exchange have increased levels of debt and debt to equity ratio so the proportion of debt still dominates in the company’s capital structure. This study intends to test empirically the impact of the investment opportunity set (IOS), managerial ownership, institutional ownership, and profitability on corporate funding decisions. The population of this research is all companies listed on the Indonesia Stock Exchange for the period 2014-2018. Samples that match the criteria based on the purposive sampling technique are 83 companies with a period of 5 years in order to obtain a result of 415 units of observations. Data were collected using the documentation method/secondary data. Data were analyzed using the panel data regression method and processed using Eviews version 9 software. The results of the research evidence that the investment opportunity set (IOS) has a significant positive effect on funding decisions, while institutional ownership and profitability have a significant negative effect on funding decisions. However, managerial ownership has no significant effect on funding decisions. For further researchers, it is suggested to develop a similar theme by adding variables that influence funding decisions, changing managerial ownership proxies, and adding IOS proxies to get better research results.